Doing Business 2007 : How to Reform - World Bank; International Finance Corporation (Washington, DC, 2012)
Doing Business 2007: How to reform is the fourth in a series of annual reports investigating the regulations that enhance business activity and those that constrain it. Doing Business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 175 economies-from Afghanistan to Zimbabwe-and over time. This publication points out how regulations affecting 10 areas of everyday business are measured: starting a business, dealing with licenses, employing workers, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts and closing a business. The indicators are used to analyze economic outcomes and identify what reforms have worked, where and why. The study stresses that there are 4 steps to successful reform: 1) Start simple and consider administrative reforms that don't need legislative changes; 2) Cut unnecessary procedures, reducing the number of bureaucrats entrepreneurs interact with; 3) Introduce standard application forms and publish as much regulatory information as possible; 4) And remember: many of the frustrations for businesses come from how regulations are administered. The internet alleviates these frustrations without changing the spirit of the regulation.